Studies on Structural, Optical, Mechanical and Thermal Properties of Undoped and Urea-doped L-Histidine Bromide(LHB) Single Crystals - P.Selvarajan4, S.E.Joema1, S.Perumal2, S.Ramalingam3, (Recent Research in Science and Technology, 2011)
Undoped and urea-doped L-Histidine Bromide (LHB) salt has been synthesized by solution method and solubility studies have been carried out. Single crystals of synthesized salts were grown by isothermal slow evaporation technique. The effect of the dopant(urea) on the growth and morphology has been investigated. Grown crystals were characterized with the aid of single crystal X-ray diffractometry (XRD) to confirm the crystal structure. Fourier Transform Infrared (FTIR) spectral analysis was performed to confirm the group ligands on the sample. UV visible transmittance studies show that the grown crystals have wide optical transparency in the entire visible region. The NLO activity of the grown crystal has been checked by second harmonic generation (SHG) test. The thermal stability has been analyzed using TG/DTA studies. Mechanical strength of the grown crystals was tested by measuring microhardness.